CORPORATE SOCIAL RESPONSIBILITY, CORPORATE GOVERNANCE DAN NILAI PERUSAHAAN BANK UMUM DI INDONESIA - Anggita, Tasya; Novita, Nova (Ibs Press, 2025)
This study examines the effect of Corporate Social Responsibility (CSR), Audit Committee, Institutional Ownership, and Self Assessment on Firm Value, as measured by the Tobin's Q ratio. CSR is measured using the natural logarithm of CSR costs, Audit Committee is measured by the number of audit committee meetings, Institutional Ownership is measured by the percentage of institutional share ownership of outstanding shares, and Self Assessment is measured by the assessment score carried out by the company. The population of this study were banking companies listed on the Indonesia Stock Exchange for the period 2020-2022. This study used a purposive sampling technique, resulting in 42 companies with a total sample of 126 observations. The method in this study is quantitative, using secondary data taken from the company's financial statements accessed through the Indonesia Stock Exchange. The data was processed using E-Views 12 with multiple linear regression analysis techniques, using a random effect model. The results showed that Self Assessment and Audit Committee had a significant effect on firm value, while CSR and Institutional Ownership did not show a significant effect on firm value.